2015
DOI: 10.1002/dev.21272
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of septohippocampal modulation of delay eyeblink conditioning

Abstract: The current study investigated the effects of disrupting the septohippocampal theta system on the developmental emergence of delay eyeblink conditioning. Theta oscillations are defined as electroencephalographic (EEG) waveforms with a frequency between 3–8 Hz. Hippocampal theta oscillations are generated by inputs from the entorhinal cortex and the medial septum. Theta activity has been shown to facilitate learning in a variety of paradigms, including delay eyeblink conditioning. Lesions of the medial septum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…Post-hoc pairwise comparisons showed that CR peak latency in the two older age groups significantly differed from the P17-19 group during S2-3 as well as S4-5 ( p s < 0.05) ( Fig 3B ). Overall, the observed changes in eyelid EMG activity were similar to those seen in previous studies [ 32 , 34 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Post-hoc pairwise comparisons showed that CR peak latency in the two older age groups significantly differed from the P17-19 group during S2-3 as well as S4-5 ( p s < 0.05) ( Fig 3B ). Overall, the observed changes in eyelid EMG activity were similar to those seen in previous studies [ 32 , 34 ].…”
Section: Resultssupporting
confidence: 89%
“…Eyeblink conditioning becomes progressively stronger between P17 and P24 in rats [ 32 , 33 ], and therefore develops during the period in which spatial memory and context conditioning develop. A previous study found that lesions of the medial septum impair acquisition of eyeblink conditioning in rat pups trained on P21-23 or P24-26, but not in pups trained on P17-19, suggesting that septohippocampal modulation of eyeblink conditioning emerges ontogenetically between P19 and P21 [ 34 ]. However, another study suggested that hippocampal function in associative learning might continue to develop past P21 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, septal lesions made at P12 impaired eye blink conditioning on P21–23, but not on P17–19 ( Harmon and Freeman, 2015 ). These results led the authors to postulate that the septohippocampal system and its subsequent control of hippocampal theta rhythm was active and able to facilitate eye blink conditioning between P19 and P21 ( Harmon and Freeman, 2015 ). Others have highlighted the relevance of this time window in the ontogeny of hippocampal theta rhythm, as rhythmic activity of inhibitory postsynaptic currents at theta frequencies first appears between P16 and P25, and these currents are disrupted by the activation of presynaptic GABA B receptors by the GABA B receptor agonist, baclofen ( Henderson and Jones, 2005 ).…”
Section: Discussionmentioning
confidence: 92%
“…In parallel to RXFP3 expression and the developmental appearance of RLN3 fibers between P15 and P17, immunohistochemical detection of Syn and its relative level of co-localization with RLN3 indicate that 'synaptic machinery' within the ascending RLN3 inputs develops later than P17 and that the NI to MS projection becomes functional after the maturation of the innervation. In support of this idea, septal lesions made at P12 impaired eye blink conditioning on P21-23, but not on P17-19 (Harmon and Freeman, 2015). These results led the authors to postulate that the septohippocampal system and its subsequent control of hippocampal theta rhythm was active and able to facilitate eye blink conditioning between P19 and P21 (Harmon and Freeman, 2015).…”
Section: Discussionmentioning
confidence: 93%